The people mover project - Mousumi, Mahfuza Khanom; Bobby, Aldrin Nippon; Kawsar-ul-Alam; Imran, Syed Parvez (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.